Hemoglobin (Hb) Val de Marne (Hb Footscray) in Brazil: the first case report - Okumura, J. V. [UNESP]; Shimauti, E. L. T.; Silva, D. G. H. [UNESP]; Torres, L. S. [UNESP]; Belini-Junior, E. [UNESP]; Oliveira, R. G. [UNESP]; Patussi, E. V.; Herrero, J. C. M.; Bonini-Domingos, C. R. [UNESP] (Funpec-editora, 2016)
Hemoglobin (Hb) variants involving alpha-chains are less common in the global population than Hb variants resulting from beta-chain alterations. Generally, alpha-chain Hb variants are caused by point mutations affecting alpha-1 and/or alpha-2 genes of the alpha-globin cluster (HBA1 and HBA2). In Brazil, the most prevalent alpha-chain Hb variant is Hb Hasharon. In this study, we present the first case of an Hb Val de Marne variant in the Americas, specifically in Brazil.
Keywords: Hemoglobin variants; Alpha-globin; HPLC